Memahami Konsep Tasybîh dalam Al-Quran: Perspektif Ahli Tafsir dan Implikasinya Bagi Pengembangan Materi Ajar Ilmu Bayan - Abdurahman, Rizki; Sabarudin, Ikbal; Hardianti, Mida (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2024)
The concept of tasybîh in bayan science needs to be studied more deeply regarding theory and application in understanding Quranic verses. This study aims to describe the concept of tasybîh in the Quran according to the views of exegetes as material for the development of bayan science teaching materials. This research uses a descriptive qualitative approach with a literature study method. The primary data sources in this study are books that discuss Quranic balaghah, namely al-Itqan fi Ulum al-Quran, Shafwat al-Tafasir, Tafsir al-Munir, and al-I'jaz al-Balaghi. The secondary sources consist of articles, books, and books related to the research topic. The data analysis technique is carried out with a content analysis model through the stages of (1) analysing and compiling data on tasybîh verses in the Quran according to the views of exegetes and (2) describing their implications for the development of bayan teaching materials. The results of this study indicate that there are several tasybîh verses in the Quran according to the views of exegetes in the four books above with various kinds of tasybîh in the perspective of bayan science, such as tasybîh mursal mujmal, tasybîh mursal mufashshal, tasybîh baligh, tasybîh tamtsili, tasybîh maqlub, and tasybîh dhimni. The results of this research data have significant contributions and implications for efforts to develop teaching materials based on Quranic studies. Abstrak Konsep tasybîh dalam ilmu bayan perlu dikaji lebih mendalam dari segi teori dan aplikasinya dalam memahami ayat-ayat Al-Quran. Penelitian ini bertujuan untuk mendeskripsikan konsep tasybîh dalam Al-Quran menurut pandangan ahli tafsir sebagai bahan pengembangan materi ajar ilmu bayan. Penelitian ini menggunakan pendekatan deskriptif kualitatif dengan metode studi pustaka. Sumber data primer dalam penelitian ini adalah kitab-kitab yang membahas balaghah Al-Quran, yaitu: al-Itqan fi Ulum al-Quran, Shafwat al-Tafasir, Tafsir al-Munir, dan al-I’jaz al-Balaghi. Sumber sekundernya terdiri dari artikel, buku, dan kitab yang terkait dengan topik penelitian. Teknik analisis data dilakukan dengan model analisis isi melalui tahapan (1) menganalisis dan menghimpun data ayat-ayat tasybîh dalam Al-Quran menurut pandangan ahli tafsir dan (2) mendeskripsikan implikasinya terhadap pengembangan materi ajar ilmu bayan. Hasil penelitian ini menunjukkan bahwa ada beberapa ayat-ayat tasybîh dalam Al-Quran menurut pandangan ahli tafsir dalam empat kitab di atas dengan berbagai macam tasybîh dalam perspektif ilmu bayan, seperti tasybîh mursal mujmal, tasybîh mursal mufashshal, tasybîh baligh, tasybîh tamtsili, tasybîh maqlub, dan tasybîh dhimni. Hasil data penelitian ini memiliki kontribusi yang siginifikan dan berimplikasi terhadap upaya pengembangan materi ajar ilmu bayan berbasis kajian Al-Quran